'That's My Job': Black Teachers' Perspectives on Helping Black Students Navigate White Supremacy. Issue 7 (10th November 2022) - Duncan, Kristen E.
ABSTRACT: This paper presents the findings of a research study that sought to understand the perspectives of exemplary Black teachers utilizing emancipatory pedagogies to help Black students navigate systems of white supremacy in a contemporary American social landscape where racism is simultaneously invisible and hypervisible. Using critical race theory, the findings of this narrative inquiry indicate that participants made their students aware of the ubiquity of racism and the inevitability that they would experience it. Findings also show that participants provided their students with opportunities to speak back to their oppression, shifted the ways they practiced emancipatory pedagogy based on the teaching and social context in which they found themselves, and learned to engage students in these ways at various points in their lives but not through teacher education. This study has implications for teachers, school administrators, teacher educators, and researchers.